- #1

murmillo

- 118

- 0

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter murmillo
- Start date

- #1

murmillo

- 118

- 0

- #2

- 22,178

- 3,305

Is there a question in there?

- #3

murmillo

- 118

- 0

Let G be a group of order 21. The Sylow 7-subgroup K must be normal, and the number of Sylow 3-subgroups is 1 or 7. Let x be a generator for K, and let y be a generator for one of the Sylow 3-subgrops H. Then x^7=1 and y^3=1, so H intersect K = {1} and therefore the product map HxK->G is injective. Since G has order 21, the product map is bijective.

OK, this following paragraph is where I'm stuck: Since K is normal, yxy^-1 is an element of K, a power of x, say x^i, where i is between 1 and 7. So the elements x and y satisfy the relations x^7=1, y^3=1, yx=(x^i)y. OK, this makes sense. But, says Artin, the relation y^3 restricts the possible exponents i:

x=(y^3)(x)(y^-3) = (y^2)(x^i)(y^-2) = y(x^(i^2))(y^-1)=x^(i^3)).

I don't understand the step after (y^2)(x^i)(y^-2). I understand that x is a generator of K, but is he saying that any generator g of K satisfies yxy^-1=g^i? Because we have

(y^2)(x^i)(y^-2) = y(y(x^i)y^-1)y^-1, and it seems that he's saying that y(x^i)y^-1 = x^(i^2)). So x goes to x^i under conjugation by y, but why does x^i go to x^(i^2)?

- #4

VietDao29

Homework Helper

- 1,426

- 3

OK, this following paragraph is where I'm stuck: Since K is normal,yxy^-1 is an element of K, a power of x, say x^i, where i is between 1 and 7. So the elements x and y satisfy the relations x^7=1, y^3=1, yx=(x^i)y. OK, this makes sense. But, says Artin, the relation y^3 restricts the possible exponents i:

x=(y^3)(x)(y^-3) = (y^2)(x^i)(y^-2) = y(x^(i^2))(y^-1)=x^(i^3)).

Ok, so we know that:

[tex]yxy^{-1} = x ^ i \Rightarrow \prod_{k = 1} ^ i \left( yxy^{-1} \right) = \prod_{k = 1} ^ i (x ^ i)[/tex]

[tex]\Rightarrow y \left[ \prod_{k = 1} ^ {i - 1} \left( x y ^ {-1} y \right) \right] xy ^ {-1} = x ^ {i ^ 2}[/tex]

[tex]\Rightarrow y \left[ \prod_{k = 1} ^ {i - 1} x \right] xy ^ {-1} = x ^ {i ^ 2}[/tex]

[tex]\Rightarrow y x ^ i y ^ {-1} = x ^ {i ^ 2}[/tex]

You can do the same to obtain: [tex]y x ^ {i ^ 2} y ^ {-1} = x ^ {i ^ 3}[/tex]. :)

Hope you can get it. If you have any more questions, just don't hesitate to ask. :)

Share:

- Replies
- 6

- Views
- 460

- Replies
- 1

- Views
- 321

- Replies
- 5

- Views
- 326

- Replies
- 5

- Views
- 212

- Last Post

- Replies
- 2

- Views
- 446

- Replies
- 3

- Views
- 878

- Last Post

- Replies
- 9

- Views
- 408

- Replies
- 12

- Views
- 302

- Replies
- 14

- Views
- 310

- Last Post

- Replies
- 2

- Views
- 425